Accuracy and Prosodic Features in Oral Reading in Adolescents - Fumagalli, Julieta Carolina (2023)
Background: Reading fluency is the ability to read fast, accurate and with proper expression as well as comprehending what is read. This ability is expected to be a consolidated in High School. Main goal: The aim of this research is to show the results obtained when a Reading fluency scale designed ad hoc that includes aspects related to accuracy and prosodic was applied. Method: A sample of 39 students in the 1st year of secondary school responded to a reading aloud and comprehension task of two expository texts (1 and 2), one with punctuation (condition A) and one without punctuation (condition B), which were administered in a counterbalanced manner. Results: Fluency performance was compared according to the presentation condition of the texts (A and B), a percentile analysis and nine mixed variance analyses were performed, considering as an independent intersubject variable the fluency condition (fluent vs. non-fluent), as the intrasubject independent variable was the text punctuation condition (without vs. with punctuation) and as dependent variables the measures contemplated in the scale. Conclusions: The results show that fluent and non-fluent students show differences in prosodic aspects values.